Consideraciones Epistemológicas en Torno a la Evolución de la Ciencia Geográfica - Ortiz, Jorge; Romero, Hugo; Rovira, Adriano; Zapater, Eduardo (Revista Chilena de Humanidades, 2015)
The authors present a critica! examination of different conceptual positions of geographical studies throughout the development of this field as a science, saying that at present a way is seen of understanding space as an ecological-social phenomenon, considering man that inhabits it as a biosocial being, thus leading this science towards a clearly humanistic orientation that makes use of the general methodology of sciences in order to further its understanding. They present an outline of geographical studies in Chile and of the expansión that has taken place in the universities, together with the impact of these studies on state organisms. The article includes Tables of great utility.